The European Cancer Patient Coalition and its central role in connecting stakeholders to advance patient‐centric solutions in the mission on cancer. Issue 3 (6th February 2019) - de Lorenzo, Francesco; Apostolidis, Kathi
Abstract : There is an urgent need for solutions to the economic and social inequalities in cancer care that still exist in many European countries. Patient preferences, 'big data', mobile digital technology and molecular and genomic profiling are among the innovative research topics that connect cancer patients to comprehensive cancer centres, and link translational research to cancer diagnosis, treatment and care. The question is whether Europe can deliver the complex infrastructure needed for universal coverage and equitable access to cancer care. The European Cancer Patient Coalition (ECPC), the leading 'umbrella' cancer patient organisation in Europe, has a central role in bringing the unmet needs of patients with cancer to the forefront of cancer policy, care and research. The ECPC is a respected and reliable partner in the oncology community and has effectively collaborated with institutional stakeholders and organisations, as well as with the European Commission, on cancer research projects and in the development of tools to advance health care and cancer policies at the European and national level. The ECPC believes that innovation cannot emerge and grow without patient involvement and is fully committed to increasing patient education and contribution in cancer research through its active participation in various European cancer research programmes and educational resources. The ECPC is expected to play a major role in the mission on cancer, given its previous achievements in policy and research to help overcome the inequalities in cancer prevention, treatment, rehabilitation and survivorship care. The mission on cancer will be facilitated by active collaboration between patient organisations and scientists, clinicians, politicians and industry, with the aim of identifying important research questions regarding quality of life and social issues for cancer patients of all ages. Abstract : The European Cancer Patient Coalition (ECPC) plays a central role in bringing the unmet needs of patients with cancer to the forefront of cancer policy, care and research. The ECPC believes that innovation cannot emerge and grow without patient involvement, and is fully committed to increasing patient education and contribution in cancer research through its active participation in various European cancer research programmes and educational resources. The ECPC is expected to play a major role in the mission on cancer, given its previous achievements in policy and research to help overcome the inequalities in cancer prevention, treatment, rehabilitation and survivorship care.